INTERPRETASI IMAM AL-KULAYNĪ TERHADAP HADIS AL-THAQALAYNI DALAM PENDEKATAN SOSIO-HISTORIS - Rizaka, Maghza; Muhid, Muhid; Nurita, Andris; Khoshyatulloh, Arfedin Hamas (Faculty of Ushuluddin and Religious Studies UIN Sulthan Thaha Saifuddin Jambi, 2023)
This research discusses the hadith of al-thaqalayn, considered as the legacy of Prophet Muhammad, encompassing the Quran and Ahlul Bait. Both components have been a focal point for both Sunni and Shia communities. This dispute extends beyond religious branches, delving into fundamental principles of faith. The most conspicuous contrast lies in the concept of imamah, the belief that ‘Ali ibn Abī Ṭālib has the right to succeed the Prophet as the religious and political leader, leading to profound interpretative disparities. In comprehending the Prophet’s hadith, a socio-historical approach proves pivotal, exemplified in the work of Imam al-Kulaynī, the Kitab al-Kāfī, which lays the interpretative groundwork for the Shia community. Within this text, the hadith of al-thaqalayn reinforces the Quran and Ahlul Bait as the primary sources of Islamic law, fulfilling societal needs and deepening Imam al-Kulaynī’s legitimacy. The research methodology adopts a qualitative method, relying on content analysis of al-Kāfī by al-Kulaynī and relevant literature. This analysis highlights al-Kulaynī’s substantial influence in interpreting the hadith, addressing the social and political concerns of the Shia community. Political factors, spanning from the Buwayhiyah to the Safawiyah dynasties, have propelled the development and validation of al-Kāfī. Al-Kulaynī’s significant influence in interpreting the hadith assists in fulfilling the spiritual needs of the community, gaining substantial authority in their eyes. Through the socio-historical approach, this research uncovers the significance of al-Kulaynī’s interpretations, affirming his position as the primary reference among the Shia and his role in shaping their religious and political perspectives. Penelitian ini mengulas hadis al-thaqalayn, yang dianggap sebagai pusaka warisan Nabi Muhammad saw., mencakup al-Quran dan Ahlul Bait. Kedua komponen ini telah menjadi fokus perhatian utama bagi Sunni maupun Syi‘ah. Perselisihan ini tak terbatas pada cabang agama, melainkan mendasar pada prinsip dasar agama. Perbedaan paling mencolok adalah konsep imamah, keyakinan bahwa ‘Ali ibn Abī Ṭālib memiliki hak untuk mengambil alih peran sebagai pemimpin agama dan negara setelah Nabi, menimbulkan kesenjangan interpretatif yang mendalam. Dalam upaya memahami hadis Nabi, pendekatan sosio-historis menjadi penting. Hal ini tercermin dalam karya Imam al-Kulaynī, Kitab al-Kāfī, yang memberikan landasan interpretatif bagi Syi‘ah. Dalam kitab ini, hadis al-Thaqalayn menegaskan al-Quran dan Ahlul Bait sebagai sumber hukum utama Islam, memenuhi kebutuhan masyarakat dan memperdalam legitimasi Imam al-Kulaynī. Pendekatan penelitian menggunakan metode kualitatif, mengandalkan content analysis pada kitab al-Kāfī karya al-Kulaynī serta literatur terkait. Analisis ini menyoroti pengaruh besar al-Kulaynī dalam interpretasi hadis, menjawab kekhawatiran sosial dan politik masyarakat Syi‘ah. Faktor politik, dari dinasti Buwayhiyah hingga Safawiyah, turut mendorong perkembangan dan legitimasi kitab al-Kāfī. Pengaruh besar al-Kulaynī dalam interpretasi hadis membantu memenuhi kebutuhan spiritual masyarakat, memperoleh otoritas yang besar dalam pandangan mereka. Melalui pendekatan sosio-historis, penelitian ini mengungkap signifikansi interpretasi al-Kulaynī terhadap hadis, menegaskan posisinya sebagai pegangan utama dalam kalangan Syi‘ah serta perannya dalam menentukan pandangan agama dan politik mereka.